2019
DOI: 10.3390/biomedicines7040086
|View full text |Cite
|
Sign up to set email alerts
|

Primary Membranous Glomerulonephritis: The Role of Serum and Urine Biomarkers in Patient Management

Abstract: The detection of phospholipase A2 receptor (PLA2R) and thrombospondin domain containing 7A THSD7A among primary membranous glomerulonephritis (MGN) patients transformed the diagnosis, treatment monitoring, and prognosis. Anti-PLA2R can be detected in 70–90% of primary MGN patients while anti-THSD7A in 2–3% of anti-PLA2R negative primary MGN patients depending on the technique used. Serum and urine samples are less invasive and non-invasive, respectively, and thus can detect the presence of anti-PLA2R and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 107 publications
(120 reference statements)
1
8
0
4
Order By: Relevance
“…Patients may undergo a Biomolecules 2020, 10, 319 2 of 14 series of renal biopsy to diagnose and monitor the disease condition. The discovery of anti-PLA 2 R Ab [5] in the serum of primary MGN patients and anti-THSD7A Ab [6] among primary MGN variants who are seronegative for anti-PLA 2 R Ab changes the dimension of diagnosis monitoring of patients using different techniques like western blot, recombinant immunofluorescence, enzyme-linked immunosorbent assay (ELISA) and many others [7]. Several studies suggested that anti-PLA 2 R Ab could be used as a prognostic biomarker for primary MGN and thus, used in monitoring primary MGN patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients may undergo a Biomolecules 2020, 10, 319 2 of 14 series of renal biopsy to diagnose and monitor the disease condition. The discovery of anti-PLA 2 R Ab [5] in the serum of primary MGN patients and anti-THSD7A Ab [6] among primary MGN variants who are seronegative for anti-PLA 2 R Ab changes the dimension of diagnosis monitoring of patients using different techniques like western blot, recombinant immunofluorescence, enzyme-linked immunosorbent assay (ELISA) and many others [7]. Several studies suggested that anti-PLA 2 R Ab could be used as a prognostic biomarker for primary MGN and thus, used in monitoring primary MGN patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that anti-PLA 2 R Ab could be used as a prognostic biomarker for primary MGN and thus, used in monitoring primary MGN patients [8,9]. In addition, most studies supported the use of ELISA as a technique of choice for the detection of biomarkers (anti-PLA 2 R and anti-THSD7A) based on the following reasons: high sensitivity and specificity, ability to measure both qualitative and quantitative assays and affordability [7,10]. Despite all this progress mentioned on serum anti-PLA 2 R Ab and anti-THSD7A Ab above, urine anti-PLA 2 R and anti-THSD7A are lacking [7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other studies (18,20), this study also demonstrated that nephrotic syndrome was the most common presentation among adults with MGN. Haematuria was also a common presentation, especially among individuals with the nephritic-nephrotic syndrome (21)(22)(23), while hypertension was seen mostly as a complication when there is renal compromise or in the acute form of MGN, occurring in up to 30% of cases (9,22) similar as in this study where it was reported in 37.6% of subjects with primary MGN.…”
Section: General Characteristics Of the Subjectssupporting
confidence: 69%
“…PMN is a rare pathological finding in pediatric patients, occupies 1.5 9% of biopsies during the corresponding period [19]. There is a rarity of data about the prognosis in children with PMN due to small samples with a fairly short follow-up period.…”
Section: Discussionmentioning
confidence: 99%